Dukungan Ibu Kandung, Mertua dan Suami dengan Praktek Asi Eksklusif (0-6 Bulan) di Kampung Sereh Wilayah Puskesmas Sentani Papua - Aleda Florince oyay; Agus Sartono; Erma Handarsari (Universitas Muhammadiyah Semarang, 2020)
Health profil data of Jayapura Regency, Papua in 2014 is showed the scope of mother’s milk-feeding only 40,28%. It is increasing than in 2012 that only 28,78%. It is showed that exclusive mother’s milk-feeding program in Jayapura City is not success. Purpose of this study is for knowing relationship between the biological mother support, parent-in-law, and husband with exclusive mother’s milk-feeding practice (0-6 months) in Kampung Sereh Wilaya Puskesmas Sentani Papua. This study is analytic applying retrospective approach with case control study design, samples of this study are 69 that determined by random, which is divided into 2 groups, those are, case group (exclusive mother’s milk- feeding) and control group (not exclusive mother’s milk-feeding). Method of collecting data is applying direct interview using questionnaire sheet. Statistical analysis used Chi-Square. There are significant relationship between support of biological mother support (p=0,006), mother-in-law (p = 0,000), and husband (p = 0,007), on practice of exclusive mother’s milk-feeding. Support of biological mother, mother-in-law, and husband has a good support on practice of exclusive mother’s milk-feeding. Keywords : Biological Mother, parent-in-law, husband, Exclusive Mother’s Milk-feeding.